Asymmetric synthesis of atropisomers featuring cyclobutane boronic esters facilitated by ring-strained B-ate complexes - Yu-Wen Sun; Jia-Hui Zhao; Xin-Yu Yan; Chong-Lei Ji; Huangdi Feng; De-Wei Gao (Nature Communications)
Abstract The strain-release-driven reactions of bicyclo[1.1.0]butanes (BCBs) have received significant attention from chemists. Notably, 1,2-migratory reactions enabled by BCB-derived B-ate complexes effectively complement the reactions initiated by common BCBs. The desired products are particularly valuable for late-stage transformations due to the presence of the C–B bond. However, asymmetric reactions mediated by BCB-derived boronate complexes have progressed slowly. In this study, we develop an asymmetric synthesis of atropisomers featuring cis-cyclobutane boronic esters facilitated by 1,2-carbon or boron migration of ring-strained B-ate complexes, achieving high enantioselectivity. The reaction is compatible with various aryl, alkenyl, alkyl boronic esters and B2pin2, and shows good compatibility with natural product derivatives. Mechanistic studies are conducted to understand stereoselective control in the dynamic kinetic asymmetric transformations (DYKATs). The target products can undergo a series of transformations, further demonstrating the practicality of this methodology.